SYSTEMATIC LITERATURE REVIEW: DEVELOPMENT, CHALLENGES, AND FUTURE POLICY DIRECTIONS IN THE PERSPECTIVE OF INTERNATIONAL TAXATION - Ayu Fitria Putri; Berlika Sharla Martiza; Luk Luk Fuadah (Asosiasi Dosen Muda Indonesia, 2025)
This research aims to analyze the development, challenges, and future policy directions of international taxation through a Systematic Literature Review (SLR) approach of 25 recent articles. The findings indicate that the digital economy has introduced new challenges to the global tax system, particularly regarding the definition of permanent establishment, reporting transparency, and the harmonization of regulations across countries. Key challenges include double taxation, the taxation of digital assets, and the still-debated implementation of carbon taxes in relation to economic growth. The most frequently used theory in this study is Agency Theory, which explains the relationship between the government and taxpayers in reducing information asymmetry and preventing tax avoidance practices. Meanwhile, the dominant method employed is qualitative, with descriptive and policy analysis approaches. Several initiatives, such as the Global Minimum Tax (GloBE), have been introduced to create a fairer tax system. Future tax policies are predicted to be more adaptive, prioritizing fairness, economic incentives, and the utilization of digital technology to enhance the effectiveness and transparency of the tax system.